2018
DOI: 10.1021/acs.organomet.8b00559
|View full text |Cite
|
Sign up to set email alerts
|

Redox Series of Cyclometalated Nickel Complexes [Ni((R)Ph(R′)bpy)Br]+/0/–/2– (H–(R)Ph(R′)bpy = Substituted 6-Phenyl-2,2′-bipyridine)

Abstract: New organonickel complexes [Ni­((R)­Ph­(R′)­bpy)­Br] carrying various substituted derivatives of the tridentate –C∧N∧N ligand 6-(phenyl-2-ide)-2,2′-bipyridine (−Phbpy) were synthesized from the precursor [Ni­(COD)2] (COD = 1,5-cyclooctadiene) and the protoligands (ligand precursors) Br–(R)­Ph­(R′)­bpy. Several synthetic routes for the protoligands were studied and compared. All new compounds have been analyzed and spectroscopically characterized. From several complexes crystal and molecular structures were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 58 publications
11
33
0
Order By: Relevance
“…However, further reaction and isolation yielded grey-green materials. This is in line with earlier reports on the title complex [29,30] and related work on the complex [Ni(Mes)(bpy)Br] (Mes = 2,4,6-trimethylphenyl; bpy = 2,2 -bipyridine), which decomposes in protic solvents yielding greenish octahedral Ni(II) species [46]. Avoiding protic solvents and working in vigorously dried solvents, we heated HPhbpy with NiBr 2 in toluene, but no yield was observed after 60 h at 130 • C ( Table 1, entry 1).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…However, further reaction and isolation yielded grey-green materials. This is in line with earlier reports on the title complex [29,30] and related work on the complex [Ni(Mes)(bpy)Br] (Mes = 2,4,6-trimethylphenyl; bpy = 2,2 -bipyridine), which decomposes in protic solvents yielding greenish octahedral Ni(II) species [46]. Avoiding protic solvents and working in vigorously dried solvents, we heated HPhbpy with NiBr 2 in toluene, but no yield was observed after 60 h at 130 • C ( Table 1, entry 1).…”
Section: Resultssupporting
confidence: 94%
“…From previous work, it was known that the [Ni(Phbpy)Br] is somewhat stable and soluble in CH 2 Cl 2 ( 1 H NMR) and THF (reaction medium, crystallisation solvent). The complex has a characteristic red colour [29,30]. In the course of our investigation, we found that [Ni(Phbpy)Br] is insoluble in diethyl ether.…”
Section: Cyclonickelation Experimentsmentioning
confidence: 64%
See 3 more Smart Citations